Wide‐Range Strain Sensors Based on Highly Transparent and Supremely Stretchable Graphene/Ag‐Nanowires Hybrid Structures. Issue 36 (18th July 2016) - Li, Qi; Ullah, Zaka; Li, Weiwei; Guo, Yufen; Xu, Jianbao; Wang, Rubing; Zeng, Qi; Chen, Mingliang; Liu, Chaojun; Liu, Liwei
Abstract : The increasing demand of electronic devices for physical motion detection has encouraged the development of highly elastic strain sensors. Especially, to capture wide‐range physical movements, supremely stretchable and wide‐range strain sensors are required. Here, a novel transparent, bendable, stretchable, and wide‐range strain sensor based on a sandwich‐like stacked graphene and Ag‐nanowires hybrid structures is reported. The hybrid structures on 200% pre‐stretched polyacrylate (PAC) are patterned which possess good bendability up to 2 mm radius, impressive stretchability up to 200% and comparatively low sheet resistance ≈200 Ω sq –1 with transparency 85%. Pre‐stretched PAC technique enables the sensor to work well at extremely high strains and to sense the multidirectional strains efficiently. The Ag‐nanowires pattern on PAC is fabricated via the bubble‐template method, by which a uniform distribution of Ag‐nanowires is achieved with significant connectivity throughout the surface. This not only decreases the power consumption but also enhances the sensitivity of the strain sensor. The demonstrated strain sensor is capable to sense strains between 5% and 200%, and the response time for this sensation is <1 ms. Abstract : An efficient skin‐like wide‐range strain sensor based on graphene and silver nanowire hybrid structures is demonstrated. It can sense extremely small (≈5%) up to extremely large (≈200%) applied strains. The transparent, flexible, and extremely stretchable strain sensor consumes low power and gives a fast response for multiaxial applied strains with different values and a wide range of stress frequencies.